2020
DOI: 10.1097/bor.0000000000000679
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic hyperuricemia: is it really asymptomatic?

Abstract: Purpose of review Hyperuricemia is highly prevalent, affecting approximately 38 million individuals in the United States. However, the significance of asymptomatic hyperuricemia – hyperuricemia in the absence of gout – continues to be debated. Recent findings Asymptomatic hyperuricemia results in monosodium urate crystal deposition in tissues, which may promote chronic inflammation. Intracellularly, hyperuricemia inhibits the master regulator adenosine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
44
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(47 citation statements)
references
References 100 publications
1
44
0
2
Order By: Relevance
“…However, this finding may possibly be contradictory with previous studies, which suggest that uric acid may hinder the production of insulin via inhibiting the proliferation of beta-cells in the pancreas, as well as decreasing gene expression of insulin [ 30 , 31 ]. Therefore, the positive association between glucose and asymptomatic hyperuricemia may be scientifically plausible since several studies have stated that uric acid levels may contribute to elevated serum glucose by increasing hepatic gluconeogenesis and inhibiting insulin-mediated entry of glucose into cells [ 10 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this finding may possibly be contradictory with previous studies, which suggest that uric acid may hinder the production of insulin via inhibiting the proliferation of beta-cells in the pancreas, as well as decreasing gene expression of insulin [ 30 , 31 ]. Therefore, the positive association between glucose and asymptomatic hyperuricemia may be scientifically plausible since several studies have stated that uric acid levels may contribute to elevated serum glucose by increasing hepatic gluconeogenesis and inhibiting insulin-mediated entry of glucose into cells [ 10 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Asymptomatic hyperuricemia, hyperuricemia in individuals who have not experienced gout nor nephrolithiasis, is viewed as a non-pathological condition whilst its prevalence is estimated to range between 10 and 20% worldwide [ 10 ]. Until recently, it was thought that uric acid in the soluble form is inert and does not initiate an inflammatory response.…”
Section: Introductionmentioning
confidence: 99%
“…Hyperuricemia does not always lead to the development of gout and could be asymptomatic. However, asymptomatic hyperuricemia has been linked to a condition, such as chronic inflammatory states, kidney disease, cardiovascular disease, and metabolic syndrome [13].…”
Section: Introductionmentioning
confidence: 99%
“…The definition of the role of UA is still complex, especially due to the coexistence of risk factors such as hypertension, chronic inflammation and pathophysiological peculiarities of CKD. Recent studies have shown that soluble UA exhibits a behavioral duality acting as pro-oxidant within the cell and antioxidant in the extracellular environment 10 , 51 , 52 .…”
Section: Discussionmentioning
confidence: 99%